المثقف العربي بين الأيدلوجي والمعرفي - العرباوى، نعمة محمد إبراهيم; الحلو، حسنين جابر حيدر (جامعة الكوفة - كلية الآداب, 2019)
البحث عن صيغة فكرية مقاربة لواقع الإنسان محتاج منا إلى تعمق في أكثر مسائلنا العالقة بين محنتي الإيدلوجي والمعرفي التي توجنا بحثنا بعنوان خاص بهذا الأمر، ولاسيما أن المثقف يعيش ما بين عزلة مجتمعية وما بين هوة حضارية، لأن الثقافة التي تواجه المعاصرة في وقتنا الحالي هي ثقافة متحولة أو متحركة كما يسميها البعض لأنها كانت سائرة على أفكار في الماضي وجاءت للحاضر لبناء شخصيتها الجديدة، والثقافة التي يحيل إليها لفظ (مثقف) في خطابنا المعاصر ليست هي الثقافة كما تعلم من هذا اللفظ في الخطاب العربي القديم باعتبار تطور الإنسان في مفهومية الحضارات القديمة والحديثة والمعاصرة عبر الأبعاد الحضارية لجماعة ما يقابلها مفهوم خطابي منزل منبعث من المخاطبة الحصرية للخصوصيات المتعددة للأقوام التي عاشت في تلك الحقبة عن (نوح وعاد وثمود) وغيرهم لينتهي هذا الخطاب المنزل إلى خطاب آخر يحاكي الناس في عصر العالمية الدينية ذات الأبعاد الإنسانية في فهم الواقع البشري. إذ كان التصور الشائع عن الحضارة العربية وما فيها من ثقافات تصويرهم كشعب بدوي يعيش في صحراء واسعة ويستخدم الجمل كوسيلة وحيدة لمواصلة هؤلاء كما يقول البعض: الأعراب البدو بطبيعة الحال شغوفون بالغزو والتعصب والسلب، وهي رؤية قام بها أساتذة في علم الاجتماع، ولاية كاليفورنيا، باعتبار صورة الإسلام وحضارته وثقافة مثقفيه رسمت على أنها تؤكد على العنف وحب القتال. فنأتي هنا ونحلل قول الغرب من ثقافة العرب.. أولاً: أن تصويرهم العرب كشعب بدوي يعيش في صحراء واسعة ومكثرون بالغزو وغيره فهل هذا يعني إنهم لا يأخذون بمفاهيم التعليم مثلا -لأن البداوة لا تمنع الإنسان في التعليم وكذلك الصحراء باعتبار أغلب شعراءنا العرب كانوا يذهبون للبادية للهدوء وطلاقة اللسان ولعل قول ابن خلدون: (العلوم تكثر حين يكثر العمران وتعظم الحضارة) كان ضمن إطار تطوير المجتمع إلى الأفضل. ثانياً: إن الإسلام كعقيدة تحب الحرب والقتال حتى عند مثقفيهم، وهذا القول يحتمل احتمالين: 1. إن الإسلام أمر بقتال أعداء الله ورسله فقط وهو لا يصرح بانتهاك النفس الإنسانية حتى على غير ملة الإسلام. 2. إن بعض من الذين يسمون أنفسهم مثقفين في إطار الحضارة العربية ليست لهم قدرة على رد الأسئلة والانتقادات الدينية باعتبار أن عدم الرد يحتل ثقافة الشفافية ما أدى سلبا إلى وقوعهم في متاهات الحاضر ومنزلقات المستقبل، وأما مشكلة توزيع المهام الفكرية على أكثر من متصدي لهذا المجال ليكون قادراً على وضع النقاط على الحروف في مواجهته لهذا المعترك لابد له من وقفات، وهنا لابد أن نفهم بأن الحضارتين العربية الإسلامية والغربية لكل منها تاريخ يعمل بمعطيات ولكن مجتمعنا الإسلامي داخل حضارته فرض عليه أن يكون رسالياً إذ لا يمكن أن يكون كذلك واقعاً- إذا لم يشعل هذا المشعل- وإذا ظل سادراً في الدروب المظلمة ومغمورا بالانحراف والتمرد على طبيعة الوجود والحياة فلا يستخف أن يعمل هذا المشعل داخل الحضارة. والذي نحتاجه اليوم من مثقفينا أن يقوموا بصياغة الحياة العلمية وقولبة المواقف اليومية على أساس الإيمان بالله، وبالإحسان وأن لا يركع أمام هوى الانحراف لأن المجتمع عند ذلك لا يرحمه لأنه داخل مجتمع رسالي حضاري. بينما الحضارة الأخرى باتت تعيش حالة ضياع وأصبحت تئن وطأة الانحراف والشذوذ والفراغ الحضاري التي اعمقها مظاهر المدينة الحديثة وآخرها نار الثورة الجنسية إذ هدته الصراعات البهيمية (العصبية والوجودية والبرجماتية) مما عملت على تهديد الوجود الإنساني والأخلاقي والأفكار الإنسانية- حتى المجردة منها بالفناء والفناء الكامل لذلك وضعت في هذه مناهج فكرية تحت مسمى فلسفة ما لإنارة جانب في طرف المعرفة والوصول إلى غاية ولكنها وقعت تحت طائلة الخطأ في الوصول إلى مناهج متكاملة للفكر يمنع من الظلالة والخطأ ويعود ذلك إلى عدم وعي مثقفيها بمفاهيم الجذور الحقيقة لمشكلة المعرفة والمشكلة الحضارية.
The search for an intellectual formula approach to the reality of man needs us to deepen in the most outstanding issues between my ideological and cognitive challenges, which culminated in our research on the title of this matter, especially since the intellectual lives between the isolation of the community and the point of civilization, because the culture facing contemporary mutant culture Or a mobile as some call it because it was on the ideas of the past and came to the present to build a new character, and culture, which refers to the word (cultured) in our contemporary speech is not the culture as you learn from this word in the ancient Arab discourse, Modern and contemporary across the cultural dimensions of a group corresponding to the concept of a house speech emanating from the exclusive address of the variousities of the people who lived in that era from (Noah and Wa'd and Thamood) and others to end this speech home to another speech that mimics people in the era of world religious dimensions of human understanding of human reality . The common perception of Arab civilization and its cultures as a Bedouin people living in a vast desert and using sentences as a sole means to continue them, some say, is that the Bedouins, of course, are passionate about invasion, intolerance and looting, a vision made by sociologists in California, The image of Islam, its culture and the culture of its intellectuals were painted as proof of violence and love of fighting. Here we analyze the words of the West from the culture of the Arabs. First, that their portrayal of the Arabs as a Bedouin people living in a vast desert and frequent invasion and other, docs this mean that they do not take the concepts of education, for example - because the Bedouin does not prevent the human in education as well as the desert as most of our Arab poets were going to the desert of calm and fluency of the tongue Perhaps Ibn Khaldun said: Which abounds when the urbanization and civilization is greater) was within the framework of the development of society for the better. Second: Islam as a doctrine of love of war and fighting even when educated, and this is likely to two possibilities: 1. Islam is commanded to fight the enemies of God and his messengers only and does not declare violation of the human soul even on the religion of Islam. 2. Some of the so-called intellectuals within the framework of the Arab civilization have no ability to answer questions and religious criticism, since the non-response occupies a culture of transparency, which has led them to fall into the labyrinths of the present and the slums of the future. In order to be able to put points on the characters in the face of this scene must be stopped, and here we must understand that the Arab civilizations of Islam and Western each of the history works with data, but our Islamic community within his civilization imposed it to be a messenger as it can not be a reality - if not He lights it The torch - If Sadra remained in the dark paths and immersed in the deviation and rebellion against the nature of existence and life, it is not underestimated that this torch works within civilization. What we need today is for our intellectuals to formulate scientific life and shape everyday situations on the basis of faith in God, and charity and not kneel before the perversion of deviation because society does not have mercy on it, because it is within a civilized society. While the other civilization is living in a state of loss and has become moaning the impact of deviation and anomalies and the vacuum of civilization, which deepened the manifestations of the modern city and the latest fire of the sexual revolution as it was caused by the conflicts of the biological (neurological, existential and pragmatic), which threatened the human existence and moral and human ideas - even abstracted by the annihilation and complete annihilation In these intellectual approaches under the name of a philosophy to illuminate a side in the edge of knowledge and reach to the end but occurred under the error of access to integrated approaches to thought prevents the error and error due to the lack of awareness of intellectuals with the concepts of roots and truth did not The problem of knowledge and the problem of civilization.
Keywords: الثقافة العربية -- المثقفون العرب -- الايديولوجيا